2022
DOI: 10.3390/antiox11040629
|View full text |Cite
|
Sign up to set email alerts
|

An Olive-Derived Extract 20% Rich in Hydroxytyrosol Prevents β-Amyloid Aggregation and Oxidative Stress, Two Features of Alzheimer Disease, via SKN-1/NRF2 and HSP-16.2 in Caenorhabditis elegans

Abstract: Olive milling produces olive oil and different by-products, all of them very rich in different bioactive compounds like the phenolic alcohol hydroxytyrosol. The aim of the present study was to investigate the effects of an olive fruit extract 20% rich in hydroxytyrosol on the molecular mechanisms associated with Alzheimer disease features like Aβ- and tau- induced toxicity, as well as on oxidative stress in Caenorhabditis elegans. Moreover, characterization of the extracts, regarding the profile and content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Furthermore, hydroxytyrosol is able to ameliorate neuronal impairment via modulating mitochondrial oxidative stress, neuronal inflammation, and apoptosis [ 121 , 158 ]. In Caenorhabditis elegans models, it has been demonstrated that an olive-derived extract 20% rich in hydroxytyrosol is able to prevent the β-amyloid aggregation and oxidative stress associated to Alzheimer’s disease [ 124 , 159 ]. These effects have been associated with the increased gene expression of the SKN-1/NRF2 transcription factor and the overexpression of HSP-16.2.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Furthermore, hydroxytyrosol is able to ameliorate neuronal impairment via modulating mitochondrial oxidative stress, neuronal inflammation, and apoptosis [ 121 , 158 ]. In Caenorhabditis elegans models, it has been demonstrated that an olive-derived extract 20% rich in hydroxytyrosol is able to prevent the β-amyloid aggregation and oxidative stress associated to Alzheimer’s disease [ 124 , 159 ]. These effects have been associated with the increased gene expression of the SKN-1/NRF2 transcription factor and the overexpression of HSP-16.2.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Besides OC, EVOO contains several phenolic compounds such as hydroxytyrosol, tyrosol, oleuropein, and oleacein, to list a few, which also demonstrated neuroprotective effects when tested in vitro and in vivo [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Different grades of olive oil are available based on the phenolic content, including phenolic-free refined olive oil (ROO), phenolic-rich EVOO (but low in OC), and OC-rich EVOO.…”
Section: Introductionmentioning
confidence: 99%
“…62 Up to the present, it has been reported that several compounds extend lifespan and reduce Aβ-induced toxicity in C. elegans via DAF-16, as for example royal jelly, 65 monascin, 66 dianxianning, 52 gengnianchun, 7 phosphatidylcholine, 64 Zijuan Pu'er tea extract, 67 Hibiscus sabdariffa L. extract, 68 strawberry extract, 15 oleuropein, 17 Moringa oleífera extract, 69 and hydroxytyrosol. 16 However, under our experimental conditions, DAF-16 and SOD-3 RNAi failed to delay the Aβ-induced paralysis, indicating that MH attenuation of neurotoxicity is not mediated by these pathways. On the contrary, SKN-1 and HSP-16.2 were required for MH protective effects.…”
Section: Discussionmentioning
confidence: 55%
“…It would be interesting, for future research, to assess whether MH, in addition to reducing the aggregation of the Aβ peptide, is capable of reducing Aβ oligomers, since it is well known that they are more toxic than Aβ monomers and have been related to memory loss and severity of dementia 13,52 Aβ oligomers may damage neurons by interfering with neuron-to-neuron communication at synapses. 5 Many other natural compounds, such as betaine, 49 Ginkgo biloba extract, 7 gennianchun, 7 Sideritis scardica extracts, 53 fucoidan, 54 ergothioneine, 55 frondoside A, 56 spermidine, 57 essential Oil of Acorus tatarinowii Schott, 58 allophycocyanin, 50 caffeic acid, 4 strawberry extract, 15 carnosic acid, 3 scutellarein, 59 oleuropein, 17 hydroxytyrosol, 16,59 and red-beet betalain pigments, 60 also protect C. elegans nematodes against Aβ-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation